Thinking off your feet how empirical psychology vindicates armchair philosophy - Strevens, Michael (The Belknap Press of Harvard University Press, 2019)
In an original defense of armchair philosophy, Michael Strevens seeks to restore philosophy to its traditional position as an essential part of the quest for knowledge, by reshaping debates about the nature of philosophical thinking. His approach explores experimental philosophy's methodological implications and the cognitive science of concepts.--